2017
DOI: 10.1002/cncr.30933
|View full text |Cite
|
Sign up to set email alerts
|

Combined high‐intensity local treatment and systemic therapy in metastatic head and neck squamous cell carcinoma: An analysis of the National Cancer Data Base

Abstract: BACKGROUND There is increasing evidence that primary tumor ablation can improve survival for some cancer patients with distant metastases. This may be particularly applicable to head and neck squamous cell carcinoma (HNSCC) because of its tropism for locoregional progression. METHODS This study included patients with metastatic HNSCC undergoing systemic therapy identified in the National Cancer Data Base. High-intensity local treatment was defined as radiation doses ≥ 60 Gy or oncologic resection of the prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 33 publications
5
33
0
Order By: Relevance
“…Furthermore, subgroup analysis demonstrated that the benefit for the addition of RT was consistent across all subgroups including the different primary tumor sites of the head and neck. A recent analysis of the NCDB demonstrated that intensification of treatment with either surgical resection or definitive RT was associated with improved survival and supports our results . In this study, survival outcomes were similar to our findings favoring the local treatment cohort.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, subgroup analysis demonstrated that the benefit for the addition of RT was consistent across all subgroups including the different primary tumor sites of the head and neck. A recent analysis of the NCDB demonstrated that intensification of treatment with either surgical resection or definitive RT was associated with improved survival and supports our results . In this study, survival outcomes were similar to our findings favoring the local treatment cohort.…”
Section: Discussionsupporting
confidence: 91%
“…As a biologically effective dose (BED) of at least 72 Gy 10 is needed to achieve long‐term local control, we compared the effect of delivering BED doses of 72 Gy 10 or higher on OS to that of lower doses. The BED of 72 Gy 10 was chosen a priori based on clinical data demonstrating the need for these doses (approximately 60 Gy in 30 fractions) to achieve adequate local control. Patients were excluded from the BED analysis if they had nonsensical doses such as doses >200 Gy or if they did not have a RT dose specified.…”
Section: Methodsmentioning
confidence: 99%
“…A recent analysis of the National Cancer Data Base suggested that the aggressive treatment of patients with metastatic head and neck squamous cell carcinoma using combined high‐intensity local treatment (radiation dose >60 Gy or oncologic resection of the tumor) had improved survival in comparison with patients receiving systemic therapy alone 9 . The local therapy given within the first 6 months from diagnosis had a stronger impact on survival.…”
Section: Discussionmentioning
confidence: 99%
“…7 had improved survival in comparison with patients receiving systemic therapy alone. 9 The local therapy given within the first 6 months from diagnosis had a stronger impact on survival.…”
Section: Palliative Radiation Treatment Concurrently With Chemotherapymentioning
confidence: 99%
“…Further, some have suggested that, analogous to surgery, advanced radiotherapy techniques performed at low-volume centers result in inferior outcomes and in head and neck cancer was even shown to negatively affect overall survival of patients (23). Others have recently asserted that certain cancers should be preferentially treated at academic centers because treatment at community hospitals was found to be associated with an increased risk of death (24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%